A prospective study on team-based learning combined with case-based learning in training thyroid surgery of medical intern - LUO Zhiping, GUO Zichao, SUN Hanxing, CHENG Xi, LIU Zhuoran, ZHANG Tao, YAN Jiqi, QIU Weihua, KUANG Jie, ZHAO Ren (Waike lilun yu shijian, 2022)
Objective To explore the application of team-based learning(TBL) combined with case-based learning (CBL) in training program of thyroid surgery on medical intern. Methods A prospective study was conducted in 94 interns with training program from November 2020 to June 2021 in thyroid surgery, Ruijin Hospital. The interns were grouped chronologically. Forty-six interns from November 2020 to February 2021 were included into control group and 48 interns from March 2021 to June 2021 into study group. Interns in control group were given traditional training and interns in study group with TBL with CBL training. Basic theory and knowledge, basic operative skill and ability of managing crisis were evaluated and compared between two groups. Results The basic theory and knowledge in study group were significantly better than that in control group (t=12.610, P<0.05). However, there was no significant difference in basic operative skill (t=1.566, P>0.05) and ability of managing crisis (t=1.313, P>0.05) between two groups. As for crisis management abi-lity, the team work ability (t=3.610, P<0.05) in study group was significantly better than that in control group and the completion time of patient rescue in study group (t=2.349, P<0.05) shorter than that in control group. Conclusions For learning thyroid surgery of medical intern, TBL combined with CBL training program could increase the effect of clinical teaching and team work ability of managing crisis, which would have prospects of application.